TROUBLESHOOTING TOURISM AND LEISURE AS DEVELOPMENT PROCESS IN MOZAMBIQUE - Verónica Cecílio Chiundila Vico; Francisco Fransualdo de Azevedo; Roberto Paolo Vico; Ricardo Ricci Uvinha (Cuadernos de Turismo)
This article examines the development of tourism and leisure in Mozambique, highlighting inequalities that affect its practice. Using a qualitative approach based on literature, documentary and field research, it finds that tourism stimulates corporate expansion, reinforcing the commodification of leisure and ties of dependency. It thus generates unequal relations, benefiting hegemonic stakeholders through this condition imposed on different economic and social realities. A more endogenous and solidarity-based development of tourist territories is required.